2012
DOI: 10.1097/scs.0b013e3182564ace
|View full text |Cite
|
Sign up to set email alerts
|

Cyst-Like Schwannoma on the Eyelid Margin

Abstract: Schwannomas are benign tumors originating from Schwann cells. We describe a rare case of solitary schwannoma on the eyelid margin. To our knowledge, this is the first clinical report of such a lesion on the eyelid margin, confirmed by both extensive immunohistochemical analysis and its distinctive morphology. Although schwannomas seldom undergo malignant change, they should be considered in the differential diagnosis of palpebral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Schwannoma of the eyelid margin in adults was first reported in 2007 by Lopez-Tizon et al 8 The second report was in 2012, by Cheng et al 9 The first reported case of an eyelid margin Schwannoma was a slowly enlarging 0.4 cm nodule, thought to be an inclusion cyst on the right upper eyelid margin for 1 year, which did not recur for 12 years after pentagonal full-thickness excision. The second report was a 35-year-old man who presented with a translucent, painless, cyst-like nodule with a smooth surface located on the right lower eyelid margin, resembling hidrocystoma and treated by shave excision.…”
Section: Discussionmentioning
confidence: 99%
“…Schwannoma of the eyelid margin in adults was first reported in 2007 by Lopez-Tizon et al 8 The second report was in 2012, by Cheng et al 9 The first reported case of an eyelid margin Schwannoma was a slowly enlarging 0.4 cm nodule, thought to be an inclusion cyst on the right upper eyelid margin for 1 year, which did not recur for 12 years after pentagonal full-thickness excision. The second report was a 35-year-old man who presented with a translucent, painless, cyst-like nodule with a smooth surface located on the right lower eyelid margin, resembling hidrocystoma and treated by shave excision.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical consequences of palpebral tumors might be more life threatening than those of the nasal ones. Palpebral schwannomas are rare, with less than 20 cases being reported to date to our knowledge [ 4 ]. They are more frequently less than 10 mm in size [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Palpebral schwannomas are rare, with less than 20 cases being reported to date to our knowledge [ 4 ]. They are more frequently less than 10 mm in size [ 4 ]. In the case we present, there was no cystic change as previously reported [ 4 ] but rare macrophages arranged in sheets or subendothelially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that some hereditary diseases such as neurofibromatosis, schwannomatosis and Carney complex are associated with multiple schwannomas [4] . There are only a few case reports with lower and upper eyelid involvement in the English-language literature [4][5][6][7][8][9][10][11][12][13][14][15] . In this report, an isolated schwannoma case with eyebrow involvement on the trajectory of the supraorbital nerve in a 24-year-old male patient is presented.…”
Section: Introductionmentioning
confidence: 99%